Isaiah: introduction; Revised version with notes; index and maps. Edited by Owen C. Whitehouse - Whitehouse, Owen Charles (New-century Bible, 1905)
v. 1. I-XXXIX.--V. 2. XL-LXVI. Deutero-Isaiah, XL-LV. Trito-Isaiah, LVI-LXVI.